Hubungan Inisiasi Menyusu Dini Dengan Kejadian Perdarahan Pasca Persalinan Di PMB Griya Mazaya - Khoirotul Umi Mahmudah; Sri Kustiyati (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Background: Sixty percent of all maternal deaths occur during the postpartum period and 45% of these cases occur within the first 24 hours postpartum (WHO, 2018). Steps that can prevent postpartum bleeding management include active third stage, administration of uterotonics and early initiation of breastfeeding. Oxytocin hormone levels will increase in the third stage after separation of the placenta and when early initiation of breastfeeding is carried out because the pituitary gland releases the oxytocin hormone through the baby's stomping, touching and licking of the mother's skin so that it can prevent postpartum bleeding and speed up the expulsion of the placenta naturally. Objective: To determine the effect of early initiation on the number of post-delivery events at the Griya Mazaya midwifery clinic in 2023. Method: The research method uses analytical observational analysis with case control. The research design used a retrospective approach with a sample size of 44 respondents divided into 22 groups of respondents who did IMD and did not do IMD with a data processing test using Mann Whitney. Results: The results of Mann Whitney data processing showed a p value of 0.000, which means p value < sig (0.05) thus proving that there is a difference in the incidence of post-delivery bleeding. Mothers who did IMD had less bleeding than mothers who did not do IMD. Conclusion: Management of early initiation of breastfeeding immediately after the new baby is born can significantly reduce the rate of postpartum hemorrhage.